Pengaruh Model Project Based Learning (PjBL) terhadap Hasil Belajar Metematika Siswa Kelas VII di MTsS Yati Kamang Mudik - Hamsia, Sakina Rahmi; Iltavia, Iltavia; Rahmat, Tasnim; Fitri, Haida (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of the Project Based Learning (PjBL) model on the mathematics learning outcomes of seventh-grade students at MTsS Yati Kamang Mudik. This research is quantitative research with a pre-experimental research type. The population in this study is all seventh-grade students of MTsS Yati Kamang Mudik, consisting of 2 classes with a total of 34 students. Class VII.1 was obtained as the experimental class and class VII.2 as the control class. In this regard, the research was conducted on two classes, namely the experimental class and the control class. In the experimental class, the teaching and learning process was carried out by implementing Project Based Learning (PjBL), whereas in the control class, the teaching and learning process was carried out using conventional learning. The instrument used in this study was a mathematics learning outcomes test. The data were analyzed using descriptive statistics and inferential statistics (t-test). The calculated t-test result was 1.867 with a table t-value of 1.693, so because the calculated t is greater than the table t, H0 is rejected. It is concluded that there is an effect of the Project Based Learning (PjBL) model on students' mathematics learning outcomes in class VII of MTsS Yati Kamang Mudik.